Assembly of gag-beta-galactosidase proteins into retrovirus particles. - Jones, T A (1990)
We studied the expression of beta-galactosidase (beta-gal) and 15 gag-beta-gal fusion proteins in the presence of Moloney murine leukemia virus wild-type core (gag) proteins. Analysis indicated that proteins retaining the amino-terminal portion of gag through the capsid protein-coding region were incorporated into retrovirus particles. Proteins which deleted portions of the capsid protein were assembled into virions at low efficiency, indicating the importance of capsid protein interactions in retrovirus assembly. Fusion proteins which retained the amino-terminal matrix protein of the gag polyprotein but which lacked the capsid protein were released efficiently from cells in a nonviral form. The nonviral form was characterized by a high sedimentation coefficient and a low density, suggestive of membrane vesicles. While beta-gal was present in the cytoplasm of expressing cells, all fusion constructs were associated with cellular membranes. gag-beta-gal proteins which were capable of release from cells demonstrated a two-component immunofluorescence staining pattern consisting of a circle of fluorescence around the nucleus and a punctate pattern of staining throughout the remainder of the cell. Interestingly, fusions within the matrix protein were trapped intracellularly and yielded distinct perinuclear staining patterns, possibly localizing to the rough endoplasmic reticulum and/or Golgi. This observation suggests that Moloney murine leukemia virus gag proteins travel to the plasma membrane by vesicular transport associated with the cytoplasmic face of intracellular vesicles.